Realization of Yanus Korchak ideas in the scientific works of students of pedagogical universities - Lyubov A. Kochemasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The author addresses the pedagogical heritage of the outstanding humanist educator of the twentieth century - Janusz Korczak. The article attempts to comprehend the basic conceptual ideas of Janusz Korczak from the perspective of modern requirements for the methodology of new education by attracting students to independent scientific creativity. The pedagogy of Janusz Korczak and its methodology are characterized in the context of the popularization and continuity of the ideas of humanism in1 Lyubov A. Kochemasova, Cand. Ped. Sci., Associate Professor of Pedagogy and Sociology Department.modern education. The article presents the priority areas of the competition for the implementation of the ideas of the humanist pedagogue about the self-worth of childhood, which determined the importance of the child’s right to respect, the special attention is paid to the set of rights of the child, ensuring its full development, allowing students to reveal the main provisions of the pedagogical concept and the modern context of pedagogy of Janusz Korczak. The positions of leading scientific researchers (R.A. Valeeva, I.D. Demakova, M. Kaminsk, A. Levin, I. Neverli, M. Mikhalak, etc.) are examined which develop the ideas of the teacher, analyze the problems of the theory and practice of education in the pedagogical concept of Janusz Korczak. The practical significance of the research lies in the direction of its results in improving the scientific creativity of students through the implementation of the ideas of Janusz Korczak in the international competition of research and creative works of students "In the world of wise thoughts of domestic and foreign scientists and teachers." The practical significance of the research lies in the direction of its results in enhancing students ’scientific creativity by implementing the pedagogical ideas of Janusz Korczak in the international competition of students’ research and creative works “In the world of wise thoughts of domestic and foreign academic teachers”. The presented research results can be used in higher educational institutions of Russia to solve the problems of increasing the research activities of students by reading the new pedagogical heritage of Janusz Korczak. The article will be interesting to students of educational institutions of higher education (undergraduate, graduate level), representatives of higher education, graduate students